Development of a transgenic mouse model of hepatocellular carcinoma with a liver fibrosis background. Issue 1 (December 2016) - Chung, Sook; Moon, Hyuk; Kim, Dae; Cho, Kyung; Ju, Hye-Lim; Kim, Do; Ahn, Sang; Han, Kwang-Hyub; Ro, Simon
Abstract Background Liver fibrosis and its end-stage disease, cirrhosis, are major risk factors for hepatocellular carcinoma (HCC) and present in 80 to 90 % of patients with HCC. Current genetically engineered mouse models for HCC, however, generally do not feature liver fibrosis, which is a critical discrepancy between human HCC and murine models thereof. In this study, we developed a simple transgenic mouse model of HCC within the context of a fibrotic liver. Methods Employing hydrodynamic transfection (HT), coupled with theSleeping Beauty (SB) transposon system, liver was stably transfected with transposons expressing cMyc and a short hairpin RNA down-regulating p53 (shp53). A chronic liver injury model, induced by hepatotoxic carbon tetrachloride (CCl4 ), was applied to the transgenic mice, allowing cells expressing cMyc plus shp53 to become malignant in the background of liver fibrosis. Results Livers harvested about 3 months after HT had excessive collagen deposition and activated hepatic stellate cells surrounding the tumors. Hepatocarcinogenesis was significantly accelerated in the fibrotic livers compared to those of the control, significantly decreasing the life span of the mice. The tumor incidence and average number of tumors per mouse were significantly higher in the group treated with CCl4 compared to the vehicle-treated control mice, following HT (p < 0.01). Conclusions Considering the simplicity and efficiency in generating HCC for fibrotic livers, the transgenic HCC model has the potential to be effectively used in preclinical testing of HCC anticancer therapy and in studies of hepatocarcinogenesis in fibrotic livers.